Development of a Culturally Specific Leadership Curriculum through Community-Based Participatory Research and Popular Education - Connie Kim Yen Nguyen-Truong; Jacqueline Leung; Kapiolani Micky (JMIR Publications, 2020)
Background: The purpose of this innovative capacity building pilot project was to develop, implement, and evaluate a nine-workshop curriculum, Rekki Lemnak [Thinking of] Parent Leadership, to prepare community and academic partners for community organizing within the Micronesian Islander community. The purpose of the partnership was to build team leadership and research capacity to lay a foundation for implementing a change in healthcare and school systems. Working collaboratively helped ensure access to shared leadership through the learning by doing approach, enabling a culturally responsive method to build a sustainable partnership. Approach: Community-based participatory research and Popular Education tenets and reflection were used as a guide in the development of the Rekki Lemnak [Thinking of] Parent Leadership curriculum. Nine workshops (two hours for eight workshops and three hours for one workshop) were held over a period of a year. Community and academic partners developed the learning objectives, capacity building topics, experiential activities, and an evaluation on the strengths and areas for improvement. The partnership consisted of seven Micronesian Islander parent leaders who are residents from the community at large, the Micronesian Islander Community organization including the Executive Director who is a community primary researcher and certified community health worker, and a Micronesian Islander-certified community health worker staff member, and the academic primary nurse researcher and another academic nurse researcher from Washington State University. A range from five to 10 partners with an average of eight attended the workshops, of which an average of five Micronesian Islander parent leaders attended the workshops. Community partners from the Micronesian Islander Community organization and the academic primary nurse researcher co-led four workshops. Community partners from the Micronesian Islander Community organization and MI parent leaders led two workshops respectively; academic nurse researcher partners led one workshop. Outcomes: We identified three main themes: initially shy and humble MI parent leaders who through their participation transformed to empowered voices, togetherness-coming from different Islands and academia, and the need for more outreach to Micronesian Islanders. Conclusions: Key elements of the Rekki Lemnak [Thinking of] Parent Leadership curriculum may be translatable to other community and academic partnerships. Culturally responsive research is more than a process in conducting a study. This requires an ongoing investment to establish and sustain authentic partnerships to conduct research with MI communities.